Herbicides Registered for Pine Management in Florida – 2008 - Anna Osiecka; Patrick Minogue; Alan Long; Jarek Nowak; Mark Mossler (EDIS, 2009)
Revised! Circular 1475, a 14-page fact sheet by Anna Osiecka, Patrick Minogue, Alan Long, Jarek Nowak, and Mark Mossler, provides comprehensive information about the herbicides currently registered for use in Florida pine plantations. Published by the UF School of Forest Resources and Conservation, February 2009.